Influence of vegetation type on infiltration rate and capacity at Ie jue geothermal manifestation, Mount Seulawah Agam, Indonesia - Muslich Hidayat; Djufri Djufri; Hairul Basri; Nazli Ismail; Rinaldi Idroes; M. Faisi Ikhwali (Heliyon, 2024)
Ie Jue is one of the geothermal manifestation of hot water and fumaroles in the northern zone of Mount Seulawah Agam. Because hot water in the Ie Jue manifestation is derived from meteoric water, the presence of Ie Jue hot springs is determined by rain intensity and surface infiltration rates in the vicinity of the manifestation. The purpose of this research is to determine the rate of precipitation infiltration and its link to the type of flora that grows around the manifestation. Ie Jue. The 100 m line transect approach was used to determine sampling locations. Transects were placed in stratified sampling based on the four cardinal directions from the manifestation's center, namely east, south, west, and north. In each transect, three sampling stations were placed at intervals of 0 m, 50 m, and 100 m from the manifestation's midpoint. In each transect, three sampling stations were placed at intervals of 0 m, 50 m, and 100 m from the manifestation's midpoint. At each sampling point, the vegetation type was identified, and soil temperature, moisture, pH, texture, density and organic C were measured. A single ring infiltrometer was used to quantify infiltration rate at each sampling location, and the Horton equation was used to compute infiltration capacity. The results showed that the type of tree vegetation found in the south had the maximum infiltration rate of 54 cm/h - 28.8 cm/h with a constant interval of 40 min, followed by an infiltration rate of 44.4 cm/h – 8.4 cm/h for 45 min in the north with pole vegetation type. In comparison to other regions, the south and north have exceptionally quick infiltration criteria (36.87 cm/h and 29.88 cm/h, respectively). When compared to poles, shrubs, and herbs, tree-type vegetation had the highest infiltration rate. The results showed that vegetation type, soil moisture, bulk density, and soil organic C are the most important elements influencing infiltration in the Ie jue hot spring area.